Multi-objective Optimization Design of an Aviation Split Path Transmission System - Zhao Ning; Fu Chenxi; Zhao Yongzhi; Fu Bibo (Jixie chuandong)
The promoting the safety performance and lightweight are considered as the objectives,a multi-objective optimization design of an aviation split path transmission system is conducted.To measure the safety performance of the system,gear contact and bending fatigue strength are computed.Afterwards,a multi-objective optimization model that includes maximum safety factors and minimum mass is developed,with the system parameters selected as design variables.Considering the system requirements for load sharing,a dynamics model of the split path transmission system is established so that the load sharing characteristics can be quantifiably measured and restricted.Non-dominated Sorting Genetic Algorithm II（NSGA-II）is adopted to solve the model.The results show that the method promoted can effectively improve the safety performance and reduce the weight at the same time.